Vertical Flue Gas Heat Absorption Ssystem with Option for Fuel Drying (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The publication will describe research that produced vertical inglenook type innovative vertical flue gas heat absorption system with option for fuel drying. Innovative arrangement of smoke ducts will be developed for the flue gas heat absorption inglenook. The inglenook will be heating up in the bottom therefore the lower level of premises will be heated more efficiently and provide higher degree of comfort. Considering fire safety regulations above the inglenook 4 arches will be built for storing and drying firewood before burning.